Child Maltreatment Research, Policy, and Practice Contributions of Penelope K. Trickett (Advances in Child and Family Policy and Practice, 2018)
The brief provides an overview of Dr. Penelope K. Trickett's work and explores her innovations in the areas of theory, measurement, and methodology in the study of child maltreatment. It offers a summary of Dr. Trickett's seminal longitudinal studies on child maltreatment, including their influence on understanding the impact of sexual abuse and child maltreatment on female and adolescent development. Chapters examine the impact of her work on policy and practice and offer present four new empirical studies that have been directly influenced by Dr. Trickett's contributions. The brief concludes with further research recommendations to bridge the current policy and practice gaps. Topics featured in this brief include: Childhood sexual abuse and its effect on eating disorder development in females. The traumatic nature of reporting maltreatment in adolescents. Associations between adolescents' community violence exposure (CVE) and the development of aggressive behavior problems. Child sexual abuse experiences in Korea. Child Maltreatment Research, Policy, and Practice is a must-have resource for policy makers and related professionals, graduate students, and researchers in child and school psychology, family studies, public health, social work, law/criminal justice, and sociology.